Numerical solution of deuteron potential depth using python. Issue 1 (1st February 2022) - Muhammad, Adam; Alnour, I.A.
Abstract: Deuteron potential depth is hardly solvable analytically, thus this study uses a numerical method through Python programming language to calculate the depth of the potential well by coding the transcendental equation. Two different approaches were used, in which the first approach is by changing the Vin (initial value) value in the code to obtain the Vo values as an output, and the second, by keeping Vin value constant and changing the radius R values to obtain different V o values in order to find the relationship between Vo and radius R. The mean average value of Vo was found to be −37.6 MeV. The result was close to the typical potential value (−36 MeV). The relationship between the potential depth and its radius shows the potential changes with respect to the deuteron radius. Moreover, the comparison of the deuteron potential depth of the present study shows an acceptable level of consistency with those of previous studies. Among other numerical methods, Python-based solution seems to be one of the simplest and most accurate method for solving complex numerical problems.